Perubahan Organisasi Puskesmas dan Peran Akuntansi dalam Perspektif Teori Institusional - Novitasari Ayuningtyas; Sri Pujiningsih (Jurnal Akuntansi Aktual, 2019)
Abstract: This study aimed to find the significance of the actor on the change of puskesmas into BLUD in the perspective of institutional theory and accounting role. This research used a qualitative method with phenomenological approach and interpretive paradigm. The data collection was obtained through interview and documentation. The data analysis started from data collection, reduction, presentation, and conclusion or verification. The results of this study showed that the significance of actors in the transformation of puskesmas into BLUD in the perspective of Institutional Theory of Coercive Isomorphism dimention caused by the dominance of Regulation and 100 Working Days Program of Malang Regency Government. Besides, in terms of Mimetic Isomorphism, there was a private model. Then, in Normative Isomorphism dimention, there were professional actors outside the organization in adopting a certain concept related to PPK–BLUD. Meanwhile, if it was examined from the accounting role particularly Management Accounting, it intended to explore the Five Annual Business Strategies and Budget Plans (RBA). In addition to this point, from the perspective of Accounting Information System (SIA), it identified the internal control of medical supplies. Furthermore, in the aspect of Financial Accounting, it merely undertook SIMDA without understanding SAP and Accrual Accounting.Abstrak: Tujuan dari penelitian ini adalah untuk menemukan signifikansi aktor atas perubahan Puskesmas menjadi BLUD dalam perspektif Teori Institusional dan peran akuntansi. Penelitian ini menggunakan metode kualitatif dengan pendekatan fenomenologi dan paradigma interpretif. Tahapan analisis data dimulai dari pengumpulan data melalui wawancara dan dokumentasi, reduksi data, presentasi, dan penyimpulan atau verifikasi. Hasil penelitian menunjukkan bahwa signifikansi aktor pada perubahan Puskesmas menjadi BLUD dari dimensi Coercive Isomorphism dalam perspektif Teori Institusional disebabkan oleh dominasi dari Regulasi dan Program 100 Hari Kerja Pemerintah Kabupaten Malang. Disamping itu, dalam bentuk dimensi Mimetic Isomorphism, ditemukan adanya model swasta. Selanjutnya, dalam dimensi Normative Isomorphism, terdapat aktor-aktor profesional diluar organisasi yang mengadopsi konsep-konsep terkait PPK-BLUD. Sementara itu, jika diuji dari peran akuntansi—khususnya pada Akuntansi Manajemen—pemaknaan aktor dimaksudkan untuk mengenal Rencana Strategis Bisnis Lima Tahunan dan Rencana Bisnis Anggaran (RBA) Tahunan. Selain itu, pengendalian internal untuk persediaan obat-obatan diidentifikasi dari perspektif Sistem Informasi Akuntansi. Lebih lanjut, dalam aspek Akuntansi Keuangan adalah sekedar menjalankan SIMDA tanpa memahami SAP dan konsep Akuntansi Akrual.